A Macroeconomic Model with Price Flexibility. (June 2018) - Singh, Gurbachan
A simple macroeconomic model is used to show that the market failure to maintain macroeconomic stability can be due to (a) price rigidity or (b) price flexibility that allows false and abnormal prices to prevail. The macroeconomic literature typically considers the first case only; this article focuses on the second case. Besides the Keynesian fiscal policy, this article considers a Pigouvian tax–subsidy scheme; the latter can be used to correct each false price individually (this use in macroeconomics resembles the more familiar use in public economics). This helps alleviate the scarcity of instruments with policymakers. As in the writings of Keynes, price stability (or rigidity) here is a policy target rather than an assumption in the model. There has been a general need to reconsider macroeconomic models since the Great Recession of 2008; this article contributes in this endeavour. JEL: E12, E62, H20